The Essence of Restorative Justice Based on the Indonesian National Police Regulation Number 8 of 2021 on the Handling of Criminal Acts Based on Restorative Justice - Harun (Universitas Pelita Harapan, 2025)
Police Regulation Number 8 of 2021 on Handling Crimes Based on Restorative Justice aims to resolve criminal cases through peaceful agreements. However, its implementation faces several potential problems, such as perpetrators who repeat their actions, which causes the impact of the deterrent effect not to be achieved. In addition, there is a risk of extortion by the victim against the perpetrator in the peace agreement process and the absence of legal rules governing both parties not to renege on the agreement. Another factor is the difference in understanding among investigators and investigators, which makes the application of Police Regulation Number 8 of 2021 subjective. This research aims to analyze the nature, implementation, and regulation of criminal acts based on restorative justice with legal certainty and justice within the Indonesian National Police. The method used is normative legal research with the support of empirical juridical research, as well as statute approach, conceptual approach, and case approach. The results show that the nature of restorative justice is an effort to restore the original state through a process that involves all parties involved in a particular criminal offense to jointly find a harmonious solution. Restorative justice is applied in various types of criminal offenses, including fraud, embezzlement, maltreatment, and murder, which involve people's lives. To increase the effectiveness of the implementation of this principle, structured collaboration between the courts, police, prosecutors' office, and correctional institutions is necessary. This research suggests two policies: first, improving the Standard Operating Procedure of Police Regulation Number 8 of 2021 by adding guidelines for procedures for handling criminal offenses using a restorative justice approach; second, drafting a special law regulating restorative justice as a guide for all law enforcement officials.